A building integrated solar air heating thermal collector prototype: modelling, validation and case studies - Buonomano, Annamaria; Esposito, Claudio; Kalogirou, Soteris A.; Mosphiliotis, Aggelos; Palombo, Adolfo; Symeou, Zacharias (My University, 2017)
In this paper, the energy performance simulation model of a new Flat-Plate Solar Thermal Collector (FPC) prototype with air as working fluid, is presented. The collector is designed to be integrated in the building envelope. With respect to existing commercial collectors such prototype is characterized by lower initial costs. The developed model is implemented in a computer code written in MatLab for the whole building energy, economic and environmental performance analysis. Specifically, the presented model is able to predict both the active and passive effects of the building integrated solar collector. The collector simulation model was validated by means of suitable experimental data collected at Limassol (Cyprus). In order to show the features of the developed simulation code, a comprehensive case study was developed. Here, the performances of both traditional stand-alone and building integrated collectors are analysed. In particular, the examined prototype is modelled as integrated on a South building façade of a multi-floor commercial building, located in different weather zones. Simulation results show that interesting energy saving can be achieved vs. traditional reference buildings, especially in cold winter climates and high heating demands.
Keywords: Flat-Plate Solar Thermal Collector; Performance analysis